PENGELOLAAN ULAYAT OLEH MASYARAKAT LOKAL DAN PENGARUHNYA TERHADAP DEFORESTASI DI HUTAN PRODUKSI DHARMASRAYA, PROVINSI SUMATRA BARAT - Abdul Mutolib; Yonariza Yonariza; Khoirul Anam (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2020)
Satellite analysis in the forest on working area of Production Forest Management Unit (PFMU) Dharmasraya shows that there has been deforestation from 2000 to 2014. Generally, deforestation is due to the conversion of forests into plantations. Deforestation is supported by activities of trading communal land with outside community. This study aims to identify local forest management irregularities of forests claimed as ulayat lands and the impacts to deforestation. This research was conducted in the PFMU Dharmasraya, West Sumatra. Data collection was conducted from February to August 2017. The study implements qualitative research design with snowball sampling to determine the research informants. The results show that local communities contribute to deforestation in the working area of PFMU Dharmasraya through the process of trading the ulayat land. In the last 14 years, secondary forest has decreased from 28,278 to 6,118 hectares. Trading of the land is through two processes: “manaruko” and “non-manaruko”. Traditionally, the manaruko sale of the customary land is in accordance with customary law while non-manaruko sale of ulayat land is not in accordance with customary rules. This process was initiated by the ulayat rulers without “adat diisi, limbago dituang” process.